Analysis of the Public Service Quality of the PUPR Service on the Economic Growth of the Stabat Community - Egi Regi Prayoga; Muhammad Yafiz (Penerbit Jurnal Indonesia, 2022)
Public service is something that must be paid attention to because to provide satisfaction to the community. The government must of course continue to strive to improve the quality of services so that people are satisfied with the performance and services provided. This study aims to analyze the quality of public services in the administration sector at the PUPR office in Langkat district. The type of research used is qualitative research. With data collection techniques using literature studies, observations and interviews from several people in the District of Stabat. The results of this study indicate that the quality of satisfactory public services is very significant for economic growth, especially for the stabat community.